A randomized crossover study of the effect of butorphanol–lidocaine and tramadol–lidocaine on sevoflurane's minimum alveolar concentration in dogs - Marzok, Mohamed; Almubarak, Adel I.; Kandeel, Mahmoud; El-Deeb, Wael; Babiker, Hussein; Fathi El-Hawari, Sayed (Frontiers in Veterinary Science, 2023)
Inhalational anaesthesia is routinely used in small animal surgery. Selecting a suitable drug combination is vital since it may negatively affect the patient’s physiological condition. We conducted this study to examine the sparing effect of butorphanol–lidocaine (BUT–LID) and tramadol–lidocaine (TRM–LID) on sevoflurane’s minimum alveolar concentration (MAC) in 10 healthy mongrel dogs aged 1-2 years and weighing 11.5 ± 0.8 kg (mean ± SD). Sevoflurane’s MAC was measured on three separate occasions. The three dog treatment groups were control (CONT) anaesthetized only with sevoflurane, TRM–LID (TRM, i.v. 1.5 mg kg-1, then 1.3 mg kg-1 hour-1 and LID, i.v. 2 mg kg-1, then 3 mg kg-1 hour-1) or BUT–LID treatment (BUT, i.v. 0.1 mg kg-1 then 0.2 mg kg-1 hour-1 and LID, i.v. 2 mg kg-1, then 3 mg kg-1 hour-1). We hypothesized that both TRM–LID and BUT–LID would result in a significant MAC sparing effect in healthy dogs. The TRM–LID treatment resulted in a nonsignificant MAC reduction. MAC was lowered significantly in the BUT–LID group (p = 0.009). The sevoflurane MAC-sparing effects of TRM–LID and BUT–LID treatments were 7.05 ± 22.20% and 19.90 ± 5.91%, respectively, a difference that was not statistically significant (p = 0.13). Bradycardia was observed in the TRM–LID (p < 0.001) treatment. The oesophageal temperature was significantly higher for the TRM–LID treatment than the CONT (p < 0.001) treatment. No statistically significant changes were detected between the three groups in fR, PE′CO2, and MABP. In conclusion, there was a significant sparing effect after adding BUT–LID co-infusion than the control group. No sparing effect was noticed when adding TRM–LID co-infusion. However, no difference in the MAC sparing percentages between the TRM–LID and BUT–LID treatments. The BUT–LID co-infusion resulted in a sevoflurane MAC reduction superior to TRM–LID in addition to minimal cardiorespiratory changes. Both BUT-LID and TRM-LID may be clinically beneficial to dogs during anaesthesia. However, BUT-LID produced a higher sparing effect and reduction of sevoflurane MAC value.